(-42x+40)=15(-8x+244)

Simple and best practice solution for (-42x+40)=15(-8x+244) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-42x+40)=15(-8x+244) equation:


Simplifying
(-42x + 40) = 15(-8x + 244)

Reorder the terms:
(40 + -42x) = 15(-8x + 244)

Remove parenthesis around (40 + -42x)
40 + -42x = 15(-8x + 244)

Reorder the terms:
40 + -42x = 15(244 + -8x)
40 + -42x = (244 * 15 + -8x * 15)
40 + -42x = (3660 + -120x)

Solving
40 + -42x = 3660 + -120x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '120x' to each side of the equation.
40 + -42x + 120x = 3660 + -120x + 120x

Combine like terms: -42x + 120x = 78x
40 + 78x = 3660 + -120x + 120x

Combine like terms: -120x + 120x = 0
40 + 78x = 3660 + 0
40 + 78x = 3660

Add '-40' to each side of the equation.
40 + -40 + 78x = 3660 + -40

Combine like terms: 40 + -40 = 0
0 + 78x = 3660 + -40
78x = 3660 + -40

Combine like terms: 3660 + -40 = 3620
78x = 3620

Divide each side by '78'.
x = 46.41025641

Simplifying
x = 46.41025641

See similar equations:

| (-42+40)=15(-8x+244) | | -281=-6x+7(-3x-17) | | 5(7-2y)+9y=31 | | (3R/4)-(4/5)=(7/10) | | 15=4x-7(x-6) | | 18-(14+f)=1-(4f+6) | | 6x+5(-5x+13)=-68 | | -2-6x=4x+12 | | -260=-3x-5(-6+25) | | 15x+20=5x+200 | | 10-x-x=24 | | 6(2c-7)+16=2(4c-1)+8 | | 8*4n-1= | | -68=-4x+5(-x-8) | | 5x+6+8x=5+8x-3x-20-3 | | 3x+25-100=0 | | 60q+45r+75s-180=15(4q+3r+5s+11) | | -68=-4x+5 | | 5x+6+8=5+8x-3x-20-3 | | -3x+5(x-27)=-119 | | (8-z)(4z+6)=0 | | -9-3x=2x+9 | | 5x+6+8=5+8x-3-20-3 | | 37z+43=z+6(6z+5) | | 4k+2k=24 | | n-7-6=-9 | | (4z+7)/(z-19)=83/(z-19) | | -3-7a-7a=-17 | | 7x+8=13y+20 | | -5+x/-2=-2 | | 6m-6-2=22 | | (4z+7)/(z-19)=415/(5z-95) |

Equations solver categories